2019
DOI: 10.2134/agronj2018.05.0336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Generalized Likelihood Uncertainty Estimation and Markov Chain Monte Carlo Methods for Uncertainty Analysis of the ORYZA_V3 Model

Abstract: Uncertainties in crop model have attracted many attentions in recent years. The Generalized Likelihood Uncertainty Estimation (GLUE) and the Markov Chain Monte Carlo (MCMC) methods have been widely used to quantify model uncertainties for hydrological models. While few papers have focused on the comparison of these two methods for a crop model, in this study the GLUE and MCMC were applied for parameter uncertainty analysis of the rice growth model ORYZA_V3. We examined the influence of subjective factors for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Tan et al [ 84 ] contrasted results of the GLUE and MCMC approaches, assessing uncertainties of nine parameters of a crop model. The authors did not address, however, an explicit specification of parameter interactions according to the posterior joint distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al [ 84 ] contrasted results of the GLUE and MCMC approaches, assessing uncertainties of nine parameters of a crop model. The authors did not address, however, an explicit specification of parameter interactions according to the posterior joint distribution.…”
Section: Discussionmentioning
confidence: 99%
“…That seemed not to be the case in our application. Tan et al (2019) contrasted results of the GLUE and MCMC approaches, assessing uncertainties of nine parameters of a crop model. The authors did not address, however, an explicit specification of parameter interactions according to the posterior joint distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, independent and uniform priors were used in the previous studies, and the model errors between simulations and observations were assumed to be normally distributed, which has been proved to be very effective in calculating the posterior parameter distributions for a crop model (Tan et al., 2019). Thus, the likelihood function in this study can be written as: LboldY-0.16emnormalθ=i=1n12πσi2exp()()YiOi22σi2where Y i and O i are the i th simulation and observation; n is the number of observations; σ i is the variance of model error, and a constant value is assumed here.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the values of these water stress parameters in the model may be changed for current rice cultivars growing in different environments. However, in the previous studies, only crop parameters in the model have been systematically studied for sensitivity analysis and uncertainty analysis (Tan et al, 2016(Tan et al, , 2019, whereas no similar studies have been found for the drought stress parameters. Therefore, the objectives of this paper are (a) to explore the sensitivities of drought stress parameters in the ORYZA (v3) model on yield under different soil conditions and fertilizer applications, (b) to quantify the ranges and distributions of drought stress parameters, and (c) to evaluate the model performance of yield simulations under drought stress conditions.…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation